Possibilities of three Swedish wild grown macroalgae - Andersson, Lisa (2021)
Macroalgae are an important energy source in several parts of the world and the popularity of algae has increased because of the specific properties. Due to the good gelling properties of macroalgae, algae derived products such as alginates can be used as additives commonly used as stabilizers in several food items. With a changing climate, the interest in algae has increased, both because algae can easily be grown without any major impacts on the climate, as well as their versatile applicability in the food industry. In Sweden, algae is an unutilized source even though the sea is a treasure box full of eatable and usable macroalgae. This may be because of the lack of cultural connection to algae as food. This thesis is a review of current literature and thoroughly investigates Swedish grown macro algae with a focus on three specific species and their potential of uses, mainly focusing on the possibilities involving food. Information has been collected through databases, scientific articles and book chapters. The review concluded that Ulva lactuca, Saccharina latissima, Palmaria palmata have the potential of being incorporated in to different existing industries such as the food industry, pharmaceuticals, future bioplastic production, energy production and as feed and fertilizer in agriculture. Furthermore, a regulated incorporation of algae in diets and food products may result in texture improvement and show health benefits. However, rather than incorporating the algae as a whole into a diet, the algae will most likely be processed and refined into certain desired substances. Even though there is a market for algae derived substances, one may argue that macroalgae should also be incorporated in food due to its nutritional properties. U. lactuca is one of few species from the non-animal source that is rich in Vitamin B12, S. latissima is rich in dietary fibre and may be useful against obesity and P.palmata is rich in iodine and protein, and has an amino acid profile that can be better than chicken.